PENGARUH ETHICAL LEADERSHIP DAN KEPUASAN KERJA TERHADAP KINERJA: IDENTIFIKASI ORGANISASI SEBAGAI MEDIASI - Gabril Saifudin; Fauzan Almanshur (JURNAL LENTERA BISNIS, 2025)
This study aims to strengthen the theory of several researchers and determine the effect of ethical leadership and job satisfaction on employee performance with organizational identification as a mediating variable. This research was conducted at PT Turen Indah Group, namely permanent employees of Ocean Garden PT Turen Indah Group. This study uses a quantitative approach, research data collected from 72 respondents. The sampling technique in this study used proportional random samopling. Statistical Package for the Social Sciences (SPSS) was used to test the hypothesis in this study using IBM SPSS Statistics Version 26. The results of this study indicate that 1) Ethical leadership has no effect on employee performance, 2) Job satisfaction has a significant effect on employee performance, 3) organizational identification can mediate the effect of ethical leadership on employee performance, and 4) organizational identification can mediate the effect of job satisfaction on employee performance.